FAKTA ILMIAH YANG TERKANDUNG DALAM SURAH AN-NABA’ AYAT 12-16 - Moh Abd Azis; Farhan Maulana (Jurnal Ushuluddin Adab dan Dakwah, 2019)
The article entitled "scientific facts contained in the surah naba verses 12-16". Discuss the subject matter, namely how the essence contained in the verse, both from the etymological and terminological understanding and through the views of the interpreter. In reviewing the meaning and scope of the surah 12-16, the author is more likely to interpret each of the mufrodat words in the verse, also using the method of interpretation, theological, and scientific approaches. In the hadith research the author uses the Tahlili interpretation method by collecting verses that are in accordance with the topics in which there are discussion points, then analyzing with the logic of thinking induction and deduction. The result concludes that in this verse Allah has collected the mention of all plants that are grown by the earth, because there are plants that have stems and some that are not. First - the types of plants that have leafy leaves so that they are called gardens. Second - types of plants that have seeds and clumps. Some are not, so they are called ordinary plants. The mention of plants that release seeds takes precedence because it is the main food for humans. After that, other types of plants followed which were food for other types of animals. And finally the mention of gardens that produce fruits and is not a staple of human food.